2015
DOI: 10.5847/wjem.j.1920-8642.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Albuterol in the treatment of acute respiratory distress syndrome: A meta-analysis of randomized controlled trials

Abstract: BACKGROUND:This meta-analysis of randomized controlled trials aimed to systematically evaluate the value of albuterol in the treatment of patients with acute respiratory distress syndrome (ARDS).DATA SOURCES: Randomized controlled trials on albuterol treatment of ARDS from its inception to October 2014 were searched systematically. The databases searched included: PubMed, Ovid EMBASE, Ovid Cochrane, CNKI, WANFANG and VIP. The trials were screened according to the pre-designed inclusion and exclusion criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Such procedures do not necessarily involve equipment or products manufactured by the biopharmaceutical, biotechnology, or other health-related industry. However, in cases such as low-dose corticosteroids for acute respiratory distress syndromes we cannot exclude the possibility that the trials not reporting their source of funding were potentially funded by industry, but this had not been disclosed [ 40 ]. We found only one topic where all the available published trials with reported funding disclosed industry support, the evaluation of high-flow nasal cannula in adult acute respiratory failure [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such procedures do not necessarily involve equipment or products manufactured by the biopharmaceutical, biotechnology, or other health-related industry. However, in cases such as low-dose corticosteroids for acute respiratory distress syndromes we cannot exclude the possibility that the trials not reporting their source of funding were potentially funded by industry, but this had not been disclosed [ 40 ]. We found only one topic where all the available published trials with reported funding disclosed industry support, the evaluation of high-flow nasal cannula in adult acute respiratory failure [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have focused on treatment issues for ARDS. 12 However, they have been inconclusive in terms of the optimal respiratory management, volume replacement, and other treatment options. 13 We therefore performed a systematic review and metaanalysis in patients with posttraumatic ARDS to address some of the open questions addressed above.…”
mentioning
confidence: 99%
“…Furthermore, widespread coagulation cascade activation causes microvascular thrombosis and fibroproliferation (Ware and Matthay, 2000). A previous study showed that albuterol could reduce the number of ventilator-free and organ failure-free days, yet it could not improve ARDS patient survival (Wu et al, 2015). At present, despite advancements in our understanding of ARDS pathogenesis, there remains a lack of effective therapy for ARDS (Boyle et al, 2013;Boyle et al, 2014).…”
Section: Introductionmentioning
confidence: 99%